In-Vitro and In-Vivo study of indomethacin loaded gelatin nanoparticles - Kumar R.; Nagarwal R.C.; Dhanawat M.; Pandit J.K. (My University, 2025)
The present research work deals with fabrication of indomethacin loaded gelatin nanoparticles prepared by double desolvation method for controlled drug delivery. Submicron polymeric particles with size <800 nm were produced possessing narrow polydispersity index (<0.5). Entrapment efficiency varied from 27-38% depending upon particle size. No drug polymer interaction was observed by FTIR. DSC study confirmed amorphous nature of nanoparticles. The in-vitro drug release profile showed initial burst release (>20% in 1 hr) followed by controlled release (>75% in 12 hr). Among the kinetic models employed, the Higuchi model showed a better fit (R 2 > 0.9) with n <0.43 (Peppas model) indicating a Fickian type of release pattern. The batch 2GA was optimum in terms of size, entrapment efficiency and drug release. Anti-inflammatory activity of the drug loaded nanoparticles (IGNP) and pure drug solution (IDM) was studied by rat paw model and IGNP significantly (P ≤ 0.001) decreased the paw volume as compared to IDM. Pharmacokinetic study showed significant enhancement (P <0.001) of various pharmacokinetic parameters. The observed t max value was 3 h for IGNP compared to 1 h for IDM. C max of IGNP had higher value (110.81±8.53 μg/mL) compared to that of IDM (51.66±7.5 μg/mL). AUC 0-12 was 1009.78±80.24 and 194.33±46.76 μg· h/mL in IGNP and IDM respectively (relative bioavailability 500%). Further, a good in vitro-in vivo correlation established the formulation for future trials. Copyright © 2011 American Scientific Publishers All rights reserved.